2005
DOI: 10.1089/lrb.2005.3.147
|View full text |Cite
|
Sign up to set email alerts
|

Texture Analysis of Post Breast Cancer Lymphedema Ultrasound Images Obtained Using a Portable Device—A Pilot Study

Abstract: The second order measure entropy is preferable to that of the first order average pixel intensity as a measure of image texture to characterize ultrasound images of extremity lymphedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 18 publications
0
15
0
1
Order By: Relevance
“…The two points were chosen based on previous ultrasound studies. 16,19,30 However, the lateral elbow point is much less studied and the PT clinicians included the lateral elbow because this area is believed to be a common area for fibrosis and it is a consistent circumferential measurement point.…”
Section: Ultrasound Of Lymphedemamentioning
confidence: 99%
See 3 more Smart Citations
“…The two points were chosen based on previous ultrasound studies. 16,19,30 However, the lateral elbow point is much less studied and the PT clinicians included the lateral elbow because this area is believed to be a common area for fibrosis and it is a consistent circumferential measurement point.…”
Section: Ultrasound Of Lymphedemamentioning
confidence: 99%
“…PT2 took five US images at each site and analyzed the images using Matlab ( b The MathWorks, Inc., Natick, MA). On each US image, eleven square, horizontal regions of interest (ROI) 16 were created at the top of the image to capture information in the superficial tissue layers up to a depth of 4 mm. Each ROI…”
Section: Ultrasound Of Lymphedemamentioning
confidence: 99%
See 2 more Smart Citations
“…[11] Further, reports have confirmed changes in subcutaneous tissue through evaluation of the elasticity of these tissues, using ultrasound imaging. [12,13] Previous studies revealed that ultrasonography had good intra-and inter-rater reliability in evaluating the subcutaneous tissue thickness in healthy subjects. [14] Another study revealed that the compressibility of the affected arm in postmastectomy lymphedema patients decreased as compared to the contralateral arm and that the measurement of compressibility using ultrasonography with the maximal compression technique was a valuable tool for evaluating lymphedema.…”
Section: Introductionmentioning
confidence: 99%